2019
DOI: 10.3389/fcell.2019.00300
|View full text |Cite
|
Sign up to set email alerts
|

One-Carbon Metabolism Regulates Embryonic Stem Cell Fate Through Epigenetic DNA and Histone Modifications: Implications for Transgenerational Metabolic Disorders in Adults

Abstract: Human (h) and mouse (m) embryonic stem (ES) cells need specific amino acids to proliferate. mES cells require threonine (Thr) metabolism for epigenetic histone modifications. Thr is converted to glycine and acetyl CoA, and the glycine is metabolized specifically to regulate trimethylation of lysine (Lys) residue 4 in histone H3 (H3K4me3). DNA methylation and methylation of other H3 Lys residues remain unimpaired by Thr deprivation in mES cell culture medium. Similarly, hES cells require methionine (Met) to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 45 publications
0
68
0
Order By: Relevance
“…Deficiency in B12 alters the levels of total homocysteine (tHcy), methionine, methylmalonic acid (MMA) and metabolites of 1C cycle including S-adenosyl methionine (SAM) and S-adenosyl homocysteine (SAH), which is associated with various adverse pregnancy outcomes and cardiovascular complications 4 . Since epigenetic modifications play a major role on the pathogenesis of many disease states, recent research predicts that metabolites of 1C metabolism might have an intermediate effect in adverse metabolic outcomes 5 . Several observational and epidemiological studies have shown that low B12 is associated with high BMI 6 , insulin resistance (IR) 7 , increasing severity of glucose tolerance 8 and adverse lipid profiles in type 2 diabetes (T2D) 9 .…”
Section: Sdmentioning
confidence: 99%
“…Deficiency in B12 alters the levels of total homocysteine (tHcy), methionine, methylmalonic acid (MMA) and metabolites of 1C cycle including S-adenosyl methionine (SAM) and S-adenosyl homocysteine (SAH), which is associated with various adverse pregnancy outcomes and cardiovascular complications 4 . Since epigenetic modifications play a major role on the pathogenesis of many disease states, recent research predicts that metabolites of 1C metabolism might have an intermediate effect in adverse metabolic outcomes 5 . Several observational and epidemiological studies have shown that low B12 is associated with high BMI 6 , insulin resistance (IR) 7 , increasing severity of glucose tolerance 8 and adverse lipid profiles in type 2 diabetes (T2D) 9 .…”
Section: Sdmentioning
confidence: 99%
“…Blastocysts developing in a medium containing essential amino acids also produce larger fetuses. While essential amino acids support growth and development as nutrients, they also foster signaling in early embryos [1,[4][5][6]. Amino acid transport proteins are needed in plasma membranes to regulate the concentrations of essential amino acids in conceptuses, but these transporters can be overwhelmed by altered amino acid availability.…”
Section: Introductionmentioning
confidence: 99%
“…MES cells need threonine (Thr) metabolism to complete epigenetic histone modification. Thr is converted to glycine and acetyl coenzyme A, and glycine metabolism specifically regulates the trimethylation of lysine (Lys) residues in histone H3 (H3K4me3) (Van Winkle & Ryznar, 2019). In addition, we also found that the modification of L-lysine carbamylation in the old group was lower than that in the young group.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…Carbamylation is an irreversible non-enzyme modification process. The process is the side chain reaction between the decomposition product of urea and the N-terminus of protein or lysine residue, which was previously reported to be related to the ageing of proteins (Van Winkle & Ryznar, 2019). L-lysine carbamylation can promote the coordination interaction of metal ions to specific enzyme activities.…”
Section: Conclusion and Discussionmentioning
confidence: 99%